Pengaruh Bomb Tea Terhadap Tekanan Darah Pada Penderita Hipertensi Di Wilayah Kerja Puskesmas Baros - Indah Handayani; Burhanuddin Basri; Lutiyah Lutiyah (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Background: Hypertension or high blood pressure is a non-communicable disease with abnormal blood pressure condition above the normal limit, which is higher than 140/90 mmHg. Hypertension is one of the diseases without symptoms and usually called the silent killer. There are some factors that become hypertension like genetic, lifestyle which are smoking, consuming fatty foods, and consuming alcohol. Research Objectives: to determine the effect of giving Bomb Tea (butterfly pea, lemon, and isomalt) for blood pressure in hypertension sufferers in Puskesmas Baros Area, Sukabumi City. Method: the research method used in this study was pre-experimental using one group pretest-posttest design. Respondents total in this study were 16 respondents. The result will analyze by paired t-test. Result: The statistic result by paired t-test show the p-value of systolic and diastolic blood pressure is 0,000<0,05, which means there is an effect to decrease blood pressure in hypertension sufferers. Conclusion: the conclude, there is an effect in the form of reducing blood pressure in hypertension sufferers in Puskesmas Baros Area. Suggestion: the study could become an alternative treatment by consuming Bomb Tea for decreased the blood pressure for hypertension sufferers.